The Reason of Performing Code-switching and Code-mixing in Indonesian – English by the Elite People in Makassar - Baharuddin Baharuddin (Institut Agama Islam Negeri Palopo, 2022)
This article aimed at finding out reasons of code switching by the elite people. The data were obtained through questionnaire. The population was the elite people in Makassar who were divided into five groups namely doctors, government officials, lawyers, lecturers, and politicians living in Makassar. There were 100 conversation produced by 25 respondents. Those 25 respondents were asked to complete a questionnaire about their reason in codeswitching. The analysis of data in this research was carried out through the following the procedures: (1) The data were classified based on the criteria of reason (2)Â The discourse of code switching reasons was tabulated (3) The reasons of code switching were described. The result show that in term of the reasons of code switching, it is found three reasons; practicality of English, good ability of English, and lack of Indonesian expressions